In vitro antiatherogenicity of extracts from Halimeda incrassata seaweed: antioxidant activity and smooth muscle cell migration studies. - Costa-Mugica, A; Batista-González, AE; Mondejar, D; Soto, Y; Brito, V; Vázquez, AM; Brömme, D; Zaldívar-Muñoz, C; Mancini-Filho, J; Vidal-Novoa, A (Ars Pharmaceutica (Internet), 2013)
Aim: The aim of this work was to evaluate the in vitro atheroprotective potential of the seaweed Halimeda incrassata in smooth muscle cell migration and lipoprotein oxidation in relation to its antioxidant activity. Material and methods: Antioxidant activity was determinate by DPPH• radical scavenging assay and ORAC method. The inhibitory effect of the aqueous extract on LDL oxidation mediated by Cu2+ ions was determinate by TBARS and conjugated diene quantification. The effect of the seaweed aqueous extract on smooth muscle cell migration was evaluated in MOVAS-1 mouse aortic smooth muscle cell. Results: The inhibitory effect of the aqueous extract on lipoprotein oxidation mediated by Cu2+ was demonstrated. Seaweed extract caused dose-dependent inhibition of TBARS (IC50 = 0.8 mg/mL) and conjugated dienes formation. The seaweed had a high antioxidant activity in the assays performed. The activity could be related to the phenolic content of Halimeda incrassata. Conclusions: In summary, the results of this study represent a further step in the characterization of the atheroprotective action of Halimeda incrassata and indicate the seaweed could be used for a nutraceutical and/or phytoterapeutic application.